THE INFLUENCE OF KNOWLEDGE MANAGEMENT AND LEARNING ORGANIZATION ON INNOVATION IN ENHANCING ORGANIZATIONAL PERFORMANCE: A STUDY OF TAEKWONDO CLUBS/DOJANGS IN DKI JAKARTA - Pujianto, Surahman; Hermawan, Asep; Aseanty, Deasy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Lifestyle changes and increased public awareness of health have become key drivers of growing interest in sports. However, based on the 2023 Sports Development Index (IPO), public participation in sports has declined from 28.6% (2021) to 25.4% (2023). In the martial arts context, public participation in Taekwondo is only 0.2%, indicating low engagement. This study examines the influence of Knowledge Management (KM) and Learning Organization (LO) on Innovation and Organizational Performance (OP) in Taekwondo dojangs in DKI Jakarta. Using a quantitative survey and Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from 131 certified coaches. The measurement model demonstrated strong reliability and validity. The results show that KM and LO significantly enhance Innovation, indicating that effective knowledge sharing and continuous learning practices foster new training approaches and organizational improvements. However, KM and LO do not directly affect OP, and Innovation also shows no significant impact on performance. Moreover, Innovation does not mediate the relationship between KM or LO and OP. These findings suggest that while dojangs successfully develop internal capabilities for innovation, such innovations remain incremental and are not yet strategic enough to improve organizational performance. The study highlights the need for more comprehensive and strategic innovation efforts to achieve measurable performance outcomes.